A Case of Recurrent Renal Aluminum Hydroxide Stone. (9th June 2014) - Cakıroglu, Basri; Dogan, Akif Nuri; Tas, Tuncay; Gozukucuk, Ramazan; Uyanik, Bekir Sami
Abstract : Renal stone disease is characterized by the differences depending on the age, gender, and the geographic location of the patients. Seventy-five percent of the renal stone components is the calcium (Ca). The most common type of the stones is the Ca oxalate stones, while Ca phosphate, uric acid, struvite, and sistine stones are more rarely reported. Other than these types, triamterene, adenosine, silica, indinavir, and ephedrine stones are also reported in the literature as case reports. However, to the best of our knowledge, aluminum hydroxide stones was not reported reported before. Herein we will report a 38-years-old woman with the history of recurrent renal colic disease whose renal stone was determined as aluminum hydroxide stone in type. Aluminum mineral may be considered in the formation of kidney stones as it is widely used in the field of healthcare and cosmetics.